Low heritability and high phenotypic plasticity of salivary cortisol in response to environmental heterogeneity in a wild pinniped. Issue 3 (26th March 2022) - Nagel, Rebecca; Kaiser, Sylvia; Stainfield, Claire; Toscani, Camille; Fox‐Clarke, Cameron; Paijmans, Anneke J.; Costa Castro, Camila; Vendrami, David L. J.; Forcada, Jaume; Hoffman, Joseph I.
Abstract: Individuals are unique in how they interact with and respond to their environment. Correspondingly, unpredictable challenges or environmental stressors often produce an individualized response of the hypothalamic‐pituitary‐adrenal (HPA) axis and its downstream effector cortisol. We used a fully crossed, repeated measures design to investigate the factors shaping individual variation in baseline cortisol in Antarctic fur seal pups and their mothers. Saliva samples were collected from focal individuals at two breeding colonies, one with low and the other with high density, during two consecutive years of contrasting food availability. Mothers and pups were sampled concurrently at birth and shortly before weaning, while pups were additionally sampled every 20 days. We found that heritability was low for baseline cortisol, while within‐individual repeatability and among‐individual variability were high. A substantial proportion of the variation in baseline cortisol could be explained in pups and mothers by a combination of intrinsic and extrinsic factors including sex, weight, day, season, and colony of birth. Our findings provide detailed insights into the individualization of endocrine phenotypes and their genetic and environmental drivers in a wild pinniped. Furthermore, the strong associations between cortisol and life history traits that we report in fur seals could have important implications for understanding the population dynamics of species impacted by environmental change. Abstract : Stress is ubiquitous, but individuals differ. In Antarctic fur seals, individual stress levels can be explained by sex, weight, age, density, and food availability. Stress can influence how an individual behaves and interacts with its environment, so gaining a better understanding of those factors that explain variation in the stress response is important for population monitoring and conservation.